Предмет: Информатика,
автор: kira20981
решите пожалуйста. если можно на листе
Приложения:

Ответы
Автор ответа:
0
(1;3)+(1;-2)*3=(6;9)
(6;9)+(3;9)=(9;12)
чтобы чертежник вернулся в исходную точку необходимо переместить его на (-9;-12)
(-9;-12)/3=(-3;-4)
Ответ:4
(6;9)+(3;9)=(9;12)
чтобы чертежник вернулся в исходную точку необходимо переместить его на (-9;-12)
(-9;-12)/3=(-3;-4)
Ответ:4
Похожие вопросы
Предмет: Литература,
автор: aaa228ad
Предмет: Биология,
автор: qwertyroomlam
Предмет: Математика,
автор: mishafhxfh
Предмет: Алгебра,
автор: Алексей111111115